Experimental study on fire properties of interior materials used in low‐floor light‐rail trains. (13th November 2019) - An, Weiguang; Liang, Kai; Zhang, Taolin; Yin, Xiangwei; Cong, Yuzhou; Gao, Yunji; Cheng, Jianwei
Summary: In this work, cone calorimeter tests were conducted to investigate fire properties of interior materials (floor covering [FC], aluminum plate covered with paint [APCP], light diffuser [LD], and gel coat [GC]) used in low‐floor light‐rail trains. Ignition time ( t ig ) of each material decreases with the increase of radiative heat flux. The decreasing order of the four samples by ignition time under the same radiative heat flux is LD > APCP > FC > GC. The heat release rate (HRR), peak value of HRR (PHRR), time from ignition to PHRR ( t p ), fire growth rate index (FIGRA), and fire growth index (FGI) rise with the increasing radiative heat flux. For the FC, LD, and GC, single HRR peak is observed in the HRR history while three peaks are observed for APCP. For PHRR, LD > FC > APCP > GC, while for t p, GC < FC < APCP < LD. Under most conditions, the FIGRA and FGI of the FC is the highest among the four materials. Results of this work are beneficial to evaluate fire hazard of low‐floor light‐rail train and determine the emphasis of fire prevention.